2016
DOI: 10.1152/ajpcell.00301.2015
|View full text |Cite
|
Sign up to set email alerts
|

Human adipocytes from the subcutaneous superficial layer have greater adipogenic potential and lower PPAR-γ DNA methylation levels than deep layer adipocytes

Abstract: Human subcutaneous fat tissue consists of two layers, superficial adipose tissue (SAT) and deep adipose tissue (DAT). Some recent reports suggest that a disproportionate accumulation of DAT is related to obesity-associated metabolic complications. However, the differences in adipocyte function between SAT and DAT are unclear. To clarify the differences in human adipocyte characteristics between SAT and DAT, human ceiling culture-derived proliferative adipocytes (ccdPAs) were primary cultured from SAT and DAT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…It has been demonstrated that deep abdominal subcutaneous adipose tissue has a higher expression of pro-inflammatory, lipogenic and lipolytic genes, and contains higher proportions of saturated fatty acids and an increased proportion of small adipocytes [33,34]. The latter finding is in line with greater adipogenic potential and lower PPAR-γ DNA methylation levels in abdominal superficial as compared to deep-layer adipocytes [35]. Moreover, deep abdominal subcutaneous adipose tissue seems to expand disproportionally more than the superficial fat depot with increasing obesity, which predisposed toward whole-body insulin resistance and increased cardiovascular risk independent of other adiposity measures in men [34].…”
Section: Detailed Metabolic Phenotyping In Obesity: Paving the Way Fomentioning
confidence: 99%
“…It has been demonstrated that deep abdominal subcutaneous adipose tissue has a higher expression of pro-inflammatory, lipogenic and lipolytic genes, and contains higher proportions of saturated fatty acids and an increased proportion of small adipocytes [33,34]. The latter finding is in line with greater adipogenic potential and lower PPAR-γ DNA methylation levels in abdominal superficial as compared to deep-layer adipocytes [35]. Moreover, deep abdominal subcutaneous adipose tissue seems to expand disproportionally more than the superficial fat depot with increasing obesity, which predisposed toward whole-body insulin resistance and increased cardiovascular risk independent of other adiposity measures in men [34].…”
Section: Detailed Metabolic Phenotyping In Obesity: Paving the Way Fomentioning
confidence: 99%
“…We found a significantly greater area of intracytoplasmic lipid accumulation in ASCs induced to adipogenic lineage from the sSAT microenvironment together with the highest number of unilocular cells. Kosaka and collaborators showed that adipocytes from the sSAT occupy a greater area compared with the dSAT, besides having a higher quantity of these cells [ 12 ]. Previous studies have shown a higher adipogenic potential from sSAT compared with dSAT isolated from obese samples [ 11 , 13 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee and collaborators described a significant correlation between serum levels of inflammatory cytokines and adipokines with the sum of dSAT area [ 10 ]. On the other hand, two independent studies [ 11 , 12 ] revealed a higher adipogenic potential for adipocyte progenitor cells isolated from the superficial SAT (sSAT). Furthermore, gene expression analysis revealed several metabolic and anti-inflammatory genes, including adiponectin preferentially expressed in sSAT, whereas inflammatory genes are over-expressed in dSAT in human obese samples [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, decreased PPARg expression via modifications of epigenetic mechanisms may play a pivotal role in the development of obesity and diabetes (29-33, 35, 36). Few studies have shown that DNA methylation and histone modifications regulate the expression of PPARg in WAT (32,(35)(36)(37)(38)(39). First, during adipogenesis, DNA demethylation (32), as well as enrichment of active marks H3ac (40) and H3K4me3 (41,42), was observed in the PPARg promoter region that positively regulates gene expression.…”
Section: Discussionmentioning
confidence: 99%